Accuracy Verification of the Plan Evaluation Tools on Eclipse Treatment Planning System Version 8.1 - Tuntipumiamorn, Lalida; Apipunyasopon, Lukkana; Lampongpaiboon, Porntip; Damrongkijudom, Nuanpen; Liammookda, Piyanan (The ASEAN Journal of Radiology, 2023)
Objectives: Performance of the dose display and cumulative dose volume histogram(DVH) tools on Eclipse version 8.1 treatment planning system (TPS), was investigated using IAEA TRS-430 test protocol. Materials & Methods: All tests were carried out by using a simple plan on a water-like test phantom. The agreement of isodose lines with color wash and point doses, reports of the hot spot and cold spot dose, correct representation of relative and absolute dose on plan normalization and consistency of dose display with varied total dose were evaluated. For cumulative DVH. some basic parameters for DVH calculations such as volume of structure. dimension of histogram dose bin and calculation grid were investigated. Relative or absolute mode DVH. DVH dose statistics and DVH statistical reports were all the subjects of interest for assessment the cumulative DVH characteristics. Results: Consistency of the dose display tool was well maintained, since most of the deviations on all tests were found to be within ± 2 mm. For cumulative DVH. discrepancies of the calculated volumes, ranging in size from < 1 cc (optic chiasm) to > 10.000 cc (body) were shown to be within ±2 % of the known volumes. The reported doses and volumes on DVH statistical reports and graphs were exhibited accurately. Dose statistics were correctly presented. Varying histogram dose bin from 1 cGy to 5 and 10 cGy, showed the variations in DVH calculations about 2% and 5%, respectively. In the present work. size of the calculation grid showed no effect on DVH calculations. Relative or absolute mode DVH were also found to effectively perform. Discussion & Conclusion: General performance of the Eclipse 8.1 plan evaluation tool, was evaluated to be accurate for clinical implementation. For more complicated application, uncertainty in DVHs should be addressed with further investigation.